The effect of oxygenated turpentine and alpha pinene oil additives in diesel fuel on the performance, combustion, and emissions in diesel engine - Syazwana, Sapee (2023)
Diesel combustion emitted harmful gases emissions such as CO2 and NOX. Mixing diesel fuel with additives is one of the many attempts to reduce emissions from diesel combustion, as well to optimize fuel consumption of the engine. Turpentine oil and alpha pinene have high potential as bio-additive in diesel due to its properties, low viscosity, high calorific value, and high oxygen content. The aim of this research is to determine the physicochemical properties, performance, combustion, and exhaust emission characteristics of diesel with bio-additives from turpentine oil, oxygenated turpentine oil, alpha pinene oil, and oxygenated alpha pinene in a single-cylinder direct injection compression ignition engine, and to formulate new regression models of engine performance, combustion, and emission characteristics. The experiment was performed using a single cylinder unmodified Yanmar TF120M compression ignition engine at low, medium, and high loads under various engine speeds from 1200 rpm to 2400 rpm with 200 rpm interval. The additives, namely, turpentine, alpha pinene, oxygenated turpentine, and oxygenated alpha pinene were blended in diesel and used in the engine in order to identify its performance, combustion, and emission characteristics. Regression models were developed using the response surface methodology to predict the significant of engine performance and emission parameters. The results revealed that chemical composition of turpentine and oxygenated turpentine contains chemical compounds with higher volatility than diesel, density and calorific values of the test fuels with additives are higher than diesel 2.25% and 5.92%, respectively, while kinematic viscosity and cetane number of the test fuels with additives 14.76% and 5.23%, respectively, lower than diesel. The result also shows there are improvement of brake power, brake thermal efficiency, brake specific fuel consumption and exhaust gas temperature of test fuel with additives in diesel up to 7.33%, 24%, 8% and 20.06%, respectively. Peak in-cylinder pressure and peak heat release rate of test fuels with additives are 6.15% and 11.32% higher than diesel. The finding also shows carbon dioxide and nitrogen oxide exhaust emission of test fuels with additives 16.88% and 22.79% than diesel, while carbon monoxide are almost similar with diesel. Analysis of variance (ANOVA) of the experimental results at 99.5% confidence level exposed that the developed models are significant. Comparison of experimental output with those predicted by the developed models indicated close proximity having high correlation coefficients R2 for the various response variables. Overall, this study concluded that the turpentine and alpha pinene oil have a potential to be use as a bio-additive fuel for compression ignition engines in the future.